A Low Cost Approach For Using Induction Motors as Generators on Stand Alone Hydro System: Stand Alone Hydro System (SAH) as an Innovation Sustainable Operating System - Ahmad, Faizal; Smith, Nigel P. A. (Journal of Emerging Technologies and Industrial Applications, 2024)
Stand Alone Hydro System (SAH) is an Innovative Sustainable Operating Systems which running continuously to give uninterrupted electricity supply with energy storage system. This paper describes a new approach to controlling induction generators on SAH. The turbine power-speed characteristic and the relatively high magnetic saturation of modern induction machines are used to reduce the control equipment required. The implementation of the control approach is described along with considerations regarding generator selection and efficiency.